EFEKTIFITAS PENERAPAN PIDANA MATI DALAM PERSPEKTIF TINDAK PIDANA KORUPSI DI INDONESIA - Prayudi Saputra, Rian (Jurnal Pahlawan, 2022)
The death penalty in Indonesia has basically been introduced and listed in the Criminal Code, which is contained in the first book of Rules Chapter II Article 10 concerning crimes. The death penalty is basically a classic form of punishment, which is assumed to be a form of punishment capable of deterring perpetrators who commit crimes. There is only 1 (one) article regulating the death penalty in the Corruption Crime Law, namely Article 2 of Law Number 31 of 1999 in conjunction with Law Number 20 of 2001 concerning Eradication of Corruption Crimes. In the elucidation of Article 2, what is meant by "unlawfully" includes acts against the law in the formal sense as well as in the material sense, that is, even though the act is not regulated in Legislation, if the regulation is considered disgraceful because it is not in accordance with a sense of justice and the norms of social life that exist in society, then the act can be punished. Furthermore, what is meant by "certain circumstances" in this Article are circumstances that can be used as a reason for criminal prosecution of perpetrators of corruption, namely if the crime is committed against funds earmarked for disaster response, national natural disasters, riot response widespread social affairs, overcoming economic and monetary crises, as well as overcoming criminal acts of corruption. When compared with the provisions for the death penalty contained in the Law on Narcotics, the provisions for the death penalty in the Corruption Crime Law are far from perfect, even though corruption crimes and narcotics crimes are both extraordinary crimes (extra ordinary crime).